Sintesis y-alumina sebagai penyangga katalis - T. Walmiki Samadhi; S. Subagjo; Temy Nurfahmiawati (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2007)
Synthesis of y-alumina as catalist supportOf the numerous catalyst support materials utilized in the petroleum refining industry, y-alumina is one ofthe most commonly used materials, especially in the hydrotreating processes. Due to the large scale application of y-alumina, a competence in the synthesis of this material is essential in an effort to reduce the dependency of catalyst development in Indonesia on imported materials. The objectives of this research is to identify key variables in the synthesis of y-alumina according to a sol-gel procedure patented by Rana et al., which utilizes aluminum nitrate as the precursor for the formation of boehmite gel, which in turn is calcined to obtain they-alumina phase. The synthesis is undertaken in 23 full factorial experiment design involving type of base (gelling agent), concentration of base, and aging time as experimental variables. Types of base in this research are ammonium carbonate and urea. Concentrations of base and aging time were varied at 50% and 200% relative to the values set in the patented procedure. Analysis of variance (ANOVA) of the specific surface area results at a confidence level of 95% indicates the significance of type and concentration of base, and the interaction between the two variables. The highest specific surface area obtained is 195.16 m2/g, using ammonium carbonate at a concentration of 5.05 mole/mole aluminum nitrates and aging time of 20 hours. This specific surface area is higher than that stated in Rana's procedure, which is namely 175 m2/g.Keywords: y-alumina, catalyst support, specific surface area, ANOVAAbstrakDari berbagai material penyangga katalis yang digunakan dalam industri pengilangan minyak bumi, y-alumina merupakan salah satu material yang paling umum digunakan, terutama dalam proses-proses hydrotreating. Sehubungan dengan luasnya penggunaan y-alumina, sintesis material ini merupakan kompetensi kunci yang sangat penting dalam upaya mengurangi ketergantungan pengembangan katalis di Indonesia terhadap bahan-bahan impor. Tujuan penelitian ini adalah mengindentifikasi variabel-variabel kunci dalam sintesis y-alumina menurut metode sol-gel yang dipatenkan oleh Rana dkk., yang menggunakan aluminum nitrat sebagai bahan awal pembentukan gel boehmite, yang selanjutnya dikalsinasi untuk memperoleh fasa y-alumina. Sintesis dilaksanakan pada rancangan percobaan statistik 23 full factorial yang melibatkan jenis basa (sebagai gelling agent), konsentrasi basa, dan waktu aging sebagai variabel-variabel percobaan. Jenis-jenis basa yang digunakan dalam penelitian ini adalah amonium karbonal dan urea. Konsentrasi basa dan waktu aging divariasikan pada 50% dan 200% dari nilai yang digunakan dalam prosedur paten Rana dkk. Analisis varians (ANOVA) terhadap hasil pengukuran luas permukaan spesifik pada tingkat keyakinan 95% menunjukkan signifikansi jenis dan konsentrasi basa, serta interaksi antara kedua variabel tersebut. Luas permukaan spesifik tertinggi yang diperoleh adalah 195,16 m2/g, dengan menggunakan amonium karbonat pada konsentrasi 5,05 mol/mol aluminum nitrat, dan waktu aging 20 jam. Luas permukaan ini lebih tinggi daripada nilai yang dicantumkan dalam prosedur Rana, yakni sebesar 175 m2/g.Kata kunci: y-alumina, penyangga katalis, luas permukaan spesifik, ANOV